Regulation: Theory and Concepts - Dieter Bös (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
This paper first presents various simple regulatory mechanisms, in particular Vogelsang and Finsinger's iterative mechanism and Shleifer's yardstick Regulation. Unfortunately, in practical applications of these simple mechanisms the regulated utility will be able to dodge the regulator's intentions by strategic behavior. This has lead us to a treatment of informationally-demanding regulatory mechanisms which are incentive-compatible and, therefore, strategy-proof. Unfortunately, the regulator must be extremely well-informed if he wants to apply this sort of regulation: except for the actual realizations of a cost or demand characteristic and the effort of the manager, he must be perfectly informed about the situation of the regulated public utility. This is the main reason why in practice the simple RPI - X regulation prevails. Finally, in this paper we have accentuated the importance of quality regulation, which is a rather neglected field in the theory of regulation and also very often in the practice of regulation.
Keywords: L33; L51; 330; regulation; principal-agent models; privatization